Physiological Effects of Condensed Tannins from Black Currant (Ribes nigrum L.) on Isolated Rat Duodenal Contraction - Klongsiriwet, Chaweewan; Wungpanya, Janyaporn; Salaemae, Hanafarah; Thavonsuk, Suchanan; Hiranyachattada, Siriphun (Trends in Sciences, 2022)
Condensed tannins (CTs) extracted from various plants have been shown to possess antioxidant, antidiabetic, anthelmintic, anti-palatable and anti-diarrhea activity. Black currant (Ribes nigrum L.), a native plant of northern Europe and Asia, is rich in phenolic compounds, including CTs. Among the biological activities of CTs, their astringent property is likely to affect gastrointestinal motility. This study aimed to investigate the physiological effect of CTs from black currant (R. nigrum L.) leaves on isolated rat duodenal contraction. Duodenal segments were fixed in organ baths containing carbogen aerated Krebs solution at the resting tension of 0.7 - 0.8 g. The frequency, amplitude, and tone of duodenal contraction were recorded. Either CTs or acetylcholine (ACh) were cumulatively added into the bath at the concentration of between 0.001 - 10 µg/mL and 10–8 - 10–4 M, respectively. The mechanisms of CTs and ACh actions were studied using muscarinic receptor antagonist (atropine, 1.55×10–5 M) and calcium channel blocker (verapamil, 10–6 M). It is found that CTs at the concentration between 0.001 - 10 µg/mL had no direct effect on duodenal frequency, amplitude, and tone of contraction, whereas ACh showed a significant increase in tonic contraction, was suppressed by atropine. Interestingly, in the presence of atropine and verapamil, CTs showed a further significant decrease in the amplitude of duodenal contraction compared to the effect of these 2 blockers alone. It is concluded that CTs would synergize the activity of the muscarinic receptor antagonist and the calcium channel blocker at duodenal enteric neurons or smooth muscle membrane. However, the use of CTs from black currant (R. nigrum L.) leaves to treat gastro-intestinal disorders while having muscarinic receptor antagonist or calcium channel blocker need cautions. HIGHLIGHTS Black currant (Ribes nigrum L.), a native plant of northern Europe and Asia, is rich in phenolic compounds including condensed tannins (CTs) and their astringent property is likely to affect gastrointestinal motility CTs isolated from leaves of black currant (R. nigrum L.) at the physiological doses (0.001 - 10.0 µg/mL) have no direct effect on isolated rat duodenal contraction CTs may possess the synergistic or additive effect with either atropine, a nonselective muscarinic receptor, or verapamil, a calcium channel blocker on duodenal amplitude of contraction GRAPHICAL ABSTRACT